1983
DOI: 10.1136/thx.38.3.205
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic significance of Klebsiella oxytoca in acute respiratory tract infection.

Abstract: A retrospective study of all Klebsiella isolations from patients admitted to hospital with acute respiratory tract infections over a 27-month period was carried out. Ten of the Klebsiella isolations from sputum and one from a blood culture were identified as Klebsiella oxytoca. The clinical and radiological features of six patients are described. Four of these patients had lobar pneumonia, one bronchopneumonia, and one acute respiratory tract infection superimposed on cryptogenic fibrosing alveolitis. One of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…Klebsiella spp. can colonize or cause chronic upper and lower respiratory tract infections, septicemia, and severe pneumonia (18)(19)(20)(21)(23)(24)(25), and severe cases of infection were also found in our patients with K. rhinoscleromatis, K. ozaenae, and K. oxytoca.…”
Section: Discussionsupporting
confidence: 51%
“…Klebsiella spp. can colonize or cause chronic upper and lower respiratory tract infections, septicemia, and severe pneumonia (18)(19)(20)(21)(23)(24)(25), and severe cases of infection were also found in our patients with K. rhinoscleromatis, K. ozaenae, and K. oxytoca.…”
Section: Discussionsupporting
confidence: 51%
“…Four of these 11 patients had lobar pneumonia while one had bronchopneumonia, five had acute exacerbations of chronic bronchitis and one had an acute respiratory tract infection superimposed on cryptogenic fibrosing alveolitis. The authors advocated that treatment was indicated whenever this organism was isolated from the clinical specimens [15].…”
Section: Discussionmentioning
confidence: 99%
“…16 Klebsiella oxytoca has not previously been described as a pathogen in this country. It was considered the etiologic agent of respiratory tract infections in ten hospitalized patients in Edinburgh 6 with similar clinical pictures of an acute Klebsiella pneumoniae. Bacteremia was identified in one patient.…”
Section: Discussionmentioning
confidence: 99%